(untitled) (Heritage, 2022)
There is no doubt that international as well as internal legal regulation of the use of cyber space will be one of the most important topics in the near future. Namely, the development of information technologies, as well as the solutions that these technologies offer, which are used in cyberspace, will significantly improve the quality of international life structures and thus the individual structure in the future As a proposal for comparison, we cite an example of the formation of joint investigative teams, due to the fact that very often the perpetrators are from several countries and act in co-perpetration. By forming such criminal-legal teams from several countries, the goal of identifying the perpetrators, obtaining the necessary evidence and prosecuting the perpetrators of criminal acts can be achieved. As we have already emphasized, the very speed of development of modern technology, as well as the possibility of its misuse, imposes the need for every state to develop a system of defense of institutions and citizens against this type of threats. High-tech crime knows no borders, and the target can be any country, institution or individual, which leads to the conclusion that in addition to the internal regulation of this area, international cooperation is also necessary in order to adequately oppose this type of crime. Also, the calming of tensions between the most developed countries in the world, which must happen at some point, will increase the interest in solving international legal restrictions on the use of cyberspace with the aim of increasing national security in cyberspace and creating conditions for the economic development of countries and the formation of world and regional markets. . In the end, it can be concluded that the normative - legal international regulation of the use of cyberspace and the prevention of misuse of modern information and communication technologies is a prerequisite for the further progress of humanity. In the future, all this will lead to close cooperation of all internationally relevant factors in the development of common standards and rules, the definition of common response mechanisms to cyber attacks and the formation of a common security cyber infrastructure with the aim of preventing cyber attacks and increasing cyber security on a global level.